Low-carbon energy controversies - Roberts, Thomas, 1980- (Abingdon, Oxon : Routledge, 2013)
'Governments, big business and communities are coming under increased pressure to develop low carbon energy supply technologies. Within the context of the climate change debate a delicate balance has to be reached between local environmental protection and our need for reliable low carbon energy.This books brings together ten years of research conducted by the Tyndall Centre for Climate Change Research and uses a range of case studies from carbon capture and storage to on-shore wind farms to explore the complex nature of disputes between a wide variety of stakeholder groups. Topics covered include:the importance of contextthe relationship between risk and trustsense of placerole of the mediaAn invaluable resource for researchers and readers in local or national government, industry or community groups who wish to deepen their understanding of controversy around low carbon technology and how to overcome it'--
Includes bibliographical references and index.
Keywords: Renewable energy sources -- Government policy; Carbon dioxide mitigation -- Government policy; Energy policy; Environmental policy